(untitled) (Raparin Journal of Humanities (RJH), 2022)
Media economics in general and financial resources of media organizations in particular is one of the most recent economic science research topics in the areas of media and economics. In particular, after the development of media tools, media production, and message formulation in media market, the rise of expense in the Kurdistan Region of Iraq, and increase of media audience’s demands led to media organizations search for more financial resources to maintain and develop their position in the competitive market and increase profit through media production and message formulation. In this work, the new financial resources in the world’s media market are outlined, and the financial resources of the media organizations in the Kurdistan Region of Iraq in the framework of media economics are explored. Each financial resource is categorized with its level of dependency in the organizations. 8 media organizations, that are television channel, radio, digital media, and pare surveyed For this aims the researcher use description method and depend on survey with selecting 8 media organization in the Kurdistan region, for those who own television and radio channel, at the same time has digital and print media.Also this article chose ‘10’ management from high managing.Due to this research aims to explore media financing resource by media organization in the Kurdistan Region. So it concludes with some results. Which the main one is the media organization in the Kurdistan Region cannot success in getting benefit from economic resource to gain income.only %37.5 of the resource of economic resource is available in media marketing. Furthermore in the Kurdistan Region private own is come as the first media economic resource and the level of dependence on media owner as media resource is %61 to%70. Key Words: Media Economics, Media Organization, Financing Resource, Kurdistan Region.